Real-world treatment patterns and outcomes among unresectable stage III non-small cell lung cancer. - Ashwini Arunachalam; Sneha Sura; John Murphy; Paul Conkling; Jerome Goldschmidt (PLoS ONE)
Background In 2018, the treatment options for unresectable stage III non-small cell lung cancer (NSCLC) changed with durvalumab, an immune checkpoint inhibitor (ICI), which was approved for consolidation therapy following concurrent chemoradiotherapy (cCRT) without disease progression. Despite durvalumab's clinical benefit, many patients receiving this therapy developed progression. This study evaluated treatment patterns and clinical outcomes in real-world community oncology practices for patients with unresectable stage III NSCLC who received cCRT. Methods This study used The US Oncology Network's (iKnowMed) electronic health record database supplemented by chart review and included adults diagnosed with unresectable stage III NSCLC initiating cCRT between 11/01/2017 and 10/31/2019, with follow-up through 04/30/2022. cCRT included concurrent treatment with platinum-based chemotherapy and radiation therapy (+/-14 days). Real-world overall survival (rwOS) and real-world progression-free survival (rwPFS) were estimated from cCRT initiation using the Kaplan-Meier method. Results Among 426 patients, 61.5% received durvalumab post-cCRT (cCRT+durvalumab) and 38.5% did not (cCRT alone). Death (28.3%) and disease progression (22.2%) were the most common reasons for not initiating durvalumab. The median age for the cCRT+durvalumab and cCRT alone cohorts were 70 and 71 years, and 71.8% and 61.6% had Eastern Cooperative Oncology Group performance status of 0-1, respectively. 51.5% of cCRT+durvalumab discontinued durvalumab, primarily due to adverse events (35.8%) and disease progression (28.4%). Median rwOS was 50.2 (95% confidence interval [CI]:41.4, not reached) and 11.6 (95% CI:6.5,15.9) months for cCRT+durvalumab and cCRT alone, respectively. Median rwPFS was 28.5 (95% CI:23.3,36.4) months for cCRT+durvalumab and 6.3 (95% CI:4.3,9.3) months for cCRT alone, respectively. 23.7% (cCRT+durvalumab) and 26.2% (cCRT alone) received subsequent treatment, of which, 59.7% (cCRT+durvalumab) and 46.5% (cCRT alone) received ICI. Conclusion Four out of ten patients did not receive consolidation durvalumab mainly due to disease progression. Even among patients who initiated durvalumab, many patients relapsed and were retreated with ICIs. These findings underscore the need to refine treatment strategies for better outcomes in stage III unresectable NSCLC.